PENERAPAN MODEL PEMBELAJARAN COURSE REVIEW HORAY UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PKN KELAS IV SEKOLAH DASAR - Sarmita, Elma Devi; Al Juhra; Syahidin Nurdin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve students' Civics learning outcomes in elementary schools by applying the Course Review Horay learning model. This research is a Classroom Action Research using the Kemmis McTaggart model. The research procedure consists of 4 stages in each cycle, namely the planning stage, action, observation, and reflection. The subjects of this study were fourth-grade students of SD Negeri 45 Banda Aceh. Research data were obtained using descriptive statistical techniques. The results showed that there was an increase in learning activities and students' learning outcomes in Civics learning by using the Course Review Horay learning model. The increase in learning activities was observed from the activities of teachers and students. As a result, there was an increase in teacher activities from 78.09% in cycle I to 91.4% in cycle II. Furthermore, an increase in student activities also occurred, namely from 75.2% in cycle I to 91.4% in cycle II. On the other hand, the improvement in students' Civic Education (PKN) learning outcomes was 65% in cycle I and increased to 80% in cycle II. Based on this, the Course Review Horay learning model can be used as an alternative to overcome the problem of low Civic Education learning outcomes among elementary school students.